The Effect of Reproductive Health Education Method on Adolescents' Attitudes and Motivation About Sexual Health in SMAN 2 Class XI Seruyan Hilir Timur, Seruyan Regency, Central Kalimantan - Nurilhamah; Susanto, Setyo Budi (Universitas STRADA Indonesia, 2025)
The importance of reproductive health education for adolescents has become a global concern, especially in an effort to increase positive attitudes and behaviors towards sexual health. The purpose of this study is to analyze the influence of reproductive health education with the leaflet method on adolescents' attitudes and motivations about sexual health in SMAN 2 Seruyan Hilir Timur, Seruyan Regency, Central Kalimantan. The design of this study is a pre-experimentalquantitative research with a one group pre test and post test designwith the focus of the research directed to analyze the influence of reproductive health education with the leaflet method on adolescents' attitudes and motivations about sexual health at SMAN 2 Seruyan Hilir Timur, Seruyan Regency, Central Kalimantan. The total population was 63 respondents and a sample of 47 respondents was taken using the Simple Random Sampling technique. Based on the results of Wilcoxon's analysis, it was shown that the p-value of 0.000 < 0.05 then H1 was accepted, so it was concluded that there was an influence of reproductive health education with the leaflet method on adolescents' attitudes about sexual health at SMAN 2 Seruyan Hilir Timur, Seruyan Regency, Central Kalimantan. Based on the results of Wilcoxon's analysis, it shows that the p-value of 0.000 < 0.05 then H1 is accepted, so it is concluded that there is an effect of reproductive health education with the leaflet method on adolescents' motivation about sexual health at SMAN 2 Seruyan Hilir Timur, Seruyan Regency, Central Kalimantan. It is hoped that respondents will be more active in seeking and using the available information, including reading the leaflets provided carefully. In addition, adolescents are expected not to hesitate to discuss with health workers, teachers, or parents about the topic of reproductive health in order to gain a deeper understanding.